Float printing deposition to control the morphology of TiO2 photoanodes on woven textile metal substrates for TCO-free flexible dye-sensitized solar cells. Issue 71 (15th July 2016) - Yun, Min Ju; Cha, Seung I.; Seo, Seon Hee; Kim, Han Seong; Lee, Dong Y.
Abstract : In this study, a new deposition method called the floating printing method is developed to obtain the uniform and controllable deposition of electrode materials on textile or wire type substrates to be utilized in a paste printing process. Abstract : The rapid growth of portable smart devices demands wearable energy sources that convert environmental energy into electricity. Textile based solar cells are one of the most promising candidates. In particular, the rapid development of fiber or textile structured dye sensitized solar cells gives us an optimistic prospect. However, the fundamental printing process for textile based substrates, which is far different from that of TCO coated flat substrates, and the optimized morphology necessary to obtain the best performance have not yet been studied systemically. In this study, a new deposition method called the floating printing method is developed to obtain the uniform and controllable deposition of electrode materials on textile or wire type substrates to be utilized in a paste printing process. In addition, FEM analysis was performed to observe the effect of morphologies on short circuit currents and find an optimized morphology for the best energy conversion efficiency. As a result, we have found that the electron source or diffusion path enhanced electron transportation with a thin wire-top region and that a distorting diffusion path degraded the short circuit current with a thick wire-top region. TCO-free flexible DSSCs cells were prepared utilizing a metal textile substrate, a paper spacer and Pt coated carbon counter electrodes, and obtained a 4.16% energy conversion efficiency. The results can be extended to a 3-dimensional analysis considering various textile substrates.